Brain activation patterns of female multiple sclerosis patients with voiding dysfunction. Issue 3 (7th February 2020) - Khavari, Rose; Chen, Jessie; Boone, Timothy; Karmonik, Christof
Abstract: Aims: We compared brain activation patterns between female multiple sclerosis (MS) patients with voiding dysfunction (VD) and those without. We aim to expand current knowledge of supraspinal correlates of voiding initiation within a cohort of female MS patients with and without VD. Materials and Methods: Twenty‐eight ambulatory female MS patients with stable disease and lower urinary tract dysfunction were recruited for this study. Subjects were divided into group 1, without VD (n = 14), and group 2, with VD (n = 14), defined as postvoid residual urine of ≥40% of maximum cystometric capacity or need for self‐catheterization. We recorded brain activity via functional magnetic resonance imaging (fMRI) with simultaneous urodynamic testing. Average fMRI activation maps (the Student t test) were created for both groups, and areas of significant activation were identified ( P  < .05). A priori regions of interest (ROIs), identified by prior meta‐analysis to be involved in voiding, were selected. Results: Group‐averaged blood‐oxygen level‐dependent (BOLD) activation maps demonstrated significant differences between groups 1 and 2 during initiation of voiding with group 2 showing significantly lower levels of activation in all ROIs except for the left cerebellum and right cingulate gyrus. Interestingly, group 2 displayed negative BOLD signals, while group 1 displayed positive signals in the right and left pontine micturition center, right periaqueductal gray, left thalamus, and left cingulate gyrus. The activation map of group 1 was similar to healthy controls. Conclusions: Our results support the hypothesis that distinct supraspinal activation patterns exist between female MS patients with VD and those without.